PROBLEMS IN THE HYDRAULIC SYSTEMS OF HEAVY TRUCKS IN MINING OPERATIONS - Sharipov Alisher Kalbayevich (TADQIQOTLAR.UZ, 2024)
This paper explores the critical issues faced by hydraulic systems in heavy trucks used in mining operations. It discusses common problems such as hydraulic fluid leaks, contamination, overheating, and pump or valve failures, emphasizing their impact on truck performance, safety, and overall operational efficiency in harsh mining environments. The paper highlights how environmental factors like dust, extreme temperatures, and heavy loads exacerbate these issues, leading to increased downtime and maintenance costs. It also provides practical solutions, such as regular system maintenance, improved filtration, effective cooling, and better operator training, to mitigate these problems and enhance system reliability. Ultimately, the paper underscores the importance of addressing hydraulic system failures to maintain productivity and reduce the risks associated with equipment breakdowns in mining operations.